Design and Simulation of Indonesian Language Application Exam with Mobile-based End User Development Method - Aspia Manurung, Asrar (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
This paper is a descriptive study with a qualitative approach. The method of data collection is the documentation study. The results of the study show that as follows, examinations using computer-based systems have technical obstacles including the occurrence of power outages or power outages, computer specifications used on computers must be in accordance with the criteria of application requirements, examinations using computers can save the budget in financing the means of examinations , tests using a computer can be categorized as environmentally friendly because they no longer use paper, where paper-making materials come from wood. Some of the remedial actions that can be taken are as follows, solving problems regarding power outages can be overcome by having a backup power supply coming from the UPS, procuring and repairing server computer hardware that is not in accordance with the requirements criteria.. Keywords: Simulation, Mobile, Exam, End User Development.